Model Pembelajaran Discovery Learning Kurikulum Merdeka Belajar Pada Guru Sekolah Dasar - Nurwahidin, Muhammad; Habibi, Roy Kembar; Pangestu, Deviyanti; Johan Pratama, Moch (Jurnal Pengabdian Masyarakat Ilmu Pendidikan, 2023)
Community service provides training for educators in elementary schools throughout Gadingrejo District. This training provides understanding to educators to be able to apply learning creatively and innovatively to students. The learning model that is expected to be implemented is the Discovery Learning model as an appropriate learning model for students. Then the learning curriculum can begin with the implementation of the Independent Learning curriculum which has been established by the Minister of Education. The result of this training is to provide knowledge for educators at the Gadingrejo District Elementary School to use and recognize the Discovery Learning learning model and learn well about the Merdeka learning curriculum so that students can obtain independent learning by using the Pancasila student profile.